High-efficiency, polarization-independent broadband metasurface absorber with angular stability for ISM applications - Amer, Abdulrahman Ahmed Ghaleb; Shamsan, Zaid Ahmed; Algamili, Abdullah S. (Public Library of Science, 2026)
This study presents a high-efficiency broadband metasurface (MS) absorber designed for applications in the Industrial, Scientific, and Medical (ISM) frequency bands, specifically at 2.4 GHz and 5.8 GHz. The proposed absorber offers wide-angle stability and polarization insensitivity within a compact structure. It consists of a split-ring resonator (SRR) integrated with lumped resistors, hosted on an FR4 substrate and backed by a copper ground plane. An optimized 8mm air gap is introduced to improve impedance matching and extend the absorption bandwidth without increasing the overall profile. The absorber’s performance was evaluated through theoretical analysis, full-wave electromagnetic simulations, and experimental measurements. The simulated results show near-unity absorption, exceeding 98% at 2.4 GHz and 5.8 GHz under normal incidence. Additionally, the absorber achieves broadband absorption spanning 2.1 to 6.96 GHz for both transverse electric (TE) and transverse magnetic (TM) polarizations, maintaining stable operation for incidence angles up to 60°. The measured results closely agree with simulations, confirming the reliability of the design. Compared with previously reported absorbers, the proposed structure demonstrates enhanced bandwidth, compactness, and angular stability, making it a strong candidate for wireless communication, electromagnetic interference (EMI) shielding, and sensing applications.